2021
DOI: 10.1002/bimj.202000230
|View full text |Cite
|
Sign up to set email alerts
|

Sample size and power considerations for cluster randomized trials with count outcomes subject to right truncation

Abstract: Cluster randomized trials (CRTs) are widely used in epidemiological and public health studies assessing population‐level effect of group‐based interventions. One important application of CRTs is the control of vector‐borne disease, such as malaria. However, a particular challenge for designing these trials is that the primary outcome involves counts of episodes that are subject to right truncation. While sample size formulas have been developed for CRTs with clustered counts, they are not directly applicable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…There has been an extensive effort in studying the impact of unequal cluster sizes in CRTs on the estimation and inference of the average treatment effect; see, for example, Kerry et al 10 and van Breukelen et al 11 with a continuous outcome; Candel et al, 12 Li and Tong 13 for a binary outcome; Li and Tong 14 for a count outcome. The consensus from these prior investigations is that the impact of cluster size variability depends on the choice of analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been an extensive effort in studying the impact of unequal cluster sizes in CRTs on the estimation and inference of the average treatment effect; see, for example, Kerry et al 10 and van Breukelen et al 11 with a continuous outcome; Candel et al, 12 Li and Tong 13 for a binary outcome; Li and Tong 14 for a count outcome. The consensus from these prior investigations is that the impact of cluster size variability depends on the choice of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean cluster size is chosen to be mtrue‾{20,50,100}, and the degree of cluster size variation is chosen to be CV{0,0.3,0.6,0.9}. These values are in accordance with previous simulations of CRTs with unequal cluster sizes 13,14 . When the effect modifier is continuous, the marginal covariate variance, σx2, is set to 1, and the true HTE parameter, β4=δ, is among {0.10,0.15,0.25}.…”
Section: Simulation Studymentioning
confidence: 94%
See 1 more Smart Citation
“…As pointed out by the reviewers, unequal cluster sizes occur very common in real‐world CRTs. Many researchers, including our team, have investigated on how to incorporate varying cluster size into the sample size estimation by using the coefficient of variation of cluster size for different types of cluster randomization design 26,45‐47 . We expect similar results for matched‐pair CRTs with missing binary outcomes, which is an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 71%
“…Alternatively, one may pre-specify the primary analysis to be the GEE analysis with an independence working correlation and account for clustering simply via the sandwich variance. In a two-level design with equal cluster sizes, previous studies (Pan, 2001;Li and Tong, 2021) have found that GEE estimators with working exchangeable and working independence have the same asymptotic efficiency when the randomization is carried out at the cluster level (i.e. the highest level in a two-level design).…”
Section: Considerations On Using An Independence Working Correlationmentioning
confidence: 97%